Miriam,
The quadratic formula says that if you have the quadratic equation
a x^{2} + b x + c = 0
then you can find x by
For the problem that you sent the first task is to convert the equation into the form
a x^{2} + b x + c = 0
Your equation is
(x+2) (2x+3) = 6
First expand the left side to get
2 x^{2} + 7 x + 6 = 6
and the add 6 to both sides to make the right side zero.
2 x^{2} + 7 x = 0
This is now of the correct form
a x^{2} + b x + c = 0
with a = 2, b = 7 and c = 0. Thus the general quadratic expression gives
and thus x = 0 or x = ^{14}/_{4} = ^{7}/_{2}
However, no one would ever use the general quadratic expression to solve
2 x^{2} + 7 x = 0
This expression factors to yield
2 x^{2} + 7 x = x(2x + 7) = 0
and hence x = 0 or x = ^{7}/_{2}
Penny
